Optimalisasi Kemampuan Membaca Teks Berita melalui Pengembangan Bahan Ajar Berbasis Aplikasi Lumio di Kelas XI Sekolah Menengah Atas Negeri 13 Medan - Amelia, Putri; Rita, Rita; Safina, Nila (Medan Resource Center, 2025)
This study aims to optimize students' ability to read news texts by developing teaching materials based on the Lumio application. The research employed a Research and Development (R&D) approach using the 4-D development model proposed by Thiagarajan (1974) as cited in Sugiyono (2020). The research population comprised 425 students at SMA Negeri 13 Medan, with a purposive sample of 36 students from class XI-11. Data were collected through questionnaires and expert validations, incorporating both qualitative feedback and quantitative scores. Validation results from material experts indicated feasibility with scores of 85% and 95%, while media experts yielded 98% and 92%. These results demonstrate that the developed teaching materials are highly suitable for classroom implementation. The product trial at SMA Negeri 13 Medan showed a teacher response rate of 94%. Student response data from the product trial reached 88.83%, categorized as